Sistem Informasi Berbasis Web untuk Pengelolaan Unit Jalan Rel dan Jembatan di PT Kereta Api (Persero) Divre IV Tanjung Karang Barat - Rangga Agustiantino; Akmal Junaidi; Yohana Tri Utami; Favorisen Rosyking Lumbanraja (Jurnal Pepadun, 2022)
PT Kereta Api Indonesia (Persero) is a company engaged in land transportation. PT KAI employees work in units, one of which is the JJ unit in charge of recording and checking roads and railways. PT KAI (Persero) has implemented an e-Office Information System to facilitate employees' work, but the system does not fully support the JJ Unit. As a result, the JJ Unit has problems where there is a lack of time efficiency when recording work tools, staffing structures, and tracking data that still use Microsoft Excel. One solution to this problem was created: a web-based Rail Road and Bridge Unit Information System at PT KAI (Persero) Divre IV Tanjung Karang. The purpose of this research is to facilitate data searches and data updates needed in the JJ Unit. The stages of this research are data collection, system design, system development, and system testing. The result of this research is the information system of the Rail Road and Bridge Unit at PT KAI (Persero) Divre IV Tanjung Karang based on the Web. This information system was developed with PHP programming, supported by MySQL as the database. The Balsamiq MockUp application was used to design the system interface in the design phase. The system has been tested with BlackBox testing and is supported by results that are as expected. This information system has four levels of users: Senior Manager, Junior Manager, Head Office Staff, and users in each resort and station. Thus, it can be concluded that the Website-based Rail Road and Bridge Unit Information System has been successfully developed using the Waterfall method and using the PHP programming language assisted by MySQL as a database.